(untitled) (Journal of the College of Basic Education, 2023)
Due to the importance of education in the aspects of life, past and present, I chose to research this subject because of its great importance in the progress of human societies in general and the Japanese in particular, given the great progress achieved by Japan in all areas of life, surpassing many countries in the world. This is thanks to education first and the persistence of the Japanese personality to reach That progress, and the Meiji era is the beginning of wide openness to Western culture, so I will deal with it in this research, if the original heritage of Japanese civilization was combined with the incoming culture, which produced a new culture for Japan. Mori Arinori and Fukuza Yukinshi in Education in Japan, and then Epilogue.